2022
DOI: 10.1111/myc.13474
|View full text |Cite
|
Sign up to set email alerts
|

Current situation of fungal diseases in Eritrea

Abstract: The epidemiology of fungal infections in Eritrea is unknown. Most cases are under‐reported due to a lack of diagnostics. This study estimates the burden of serious fungal infections and highlights treatment and diagnostic gaps in the country. All publications related to fungal infections were identified by searches using PubMed/Medline and Google Scholar. Where no data were available, data from neighbouring countries, then sub‐Saharan African countries, then other parts of the world were considered for derivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The incidence rate of fungal infection is rapidly increasing due to environmental deterioration, drug abuse, and the descent of immune function . According to the statistics from World Health Organization (WHO), there were over 2,000,000 deaths annually worldwide caused by deep fungal infections. , Candida , Cryptococcus , and Aspergillus as the current representative pathogenic fungal strains can invade body’s internal tissues and organs to produce serious inflammatory reactions. , The current treatment pathway only relies on the relatively limited single-target antifungal drugs, including azoles, allylamine, pyrimidines, etc .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rate of fungal infection is rapidly increasing due to environmental deterioration, drug abuse, and the descent of immune function . According to the statistics from World Health Organization (WHO), there were over 2,000,000 deaths annually worldwide caused by deep fungal infections. , Candida , Cryptococcus , and Aspergillus as the current representative pathogenic fungal strains can invade body’s internal tissues and organs to produce serious inflammatory reactions. , The current treatment pathway only relies on the relatively limited single-target antifungal drugs, including azoles, allylamine, pyrimidines, etc .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the estimated incidence and prevalence of fungal diseases was found to be much higher than previously assumed or reported. For example, studies have shown that, around 8% of the Ethiopian population and 11.5% of Eritrean population suffer annually from serious fungal infections [ 14 , 15 ]. Of these infections, cryptococcal meningitis, Pneumocystis pneumonia and aspergillosis are the most frequent potentially lethal conditions.…”
Section: Introductionmentioning
confidence: 99%